"Is the Pre-cum Myth True?" An Analysis of Queries on Using Withdrawal for Contraception on Reddit [02I]. (May 2020) - Latack, Kyle; Patel, Jasmine; Moog, Dominic; Spencer, Donovan; Nguyen, Brian T.
Abstract : INTRODUCTION: Limited research and the lack of guidelines on "withdrawal" or coitus interruptus lead to inconsistent provider-patient recommendations regarding its use. Patients consequently rely on peers or online communities to learn about this neglected contraceptive method. To better understand knowledge gaps and concerns, we examined posts about withdrawal on the popular, anonymous internet discussion forum, Reddit. METHODS: Posts containing the search terms: "coitus interruptus, " "withdrawal, " "pull out, " "pre-ejaculate, " or "pre-cum" were extracted and filtered for relevant content. Data extraction was limited to gendered forums/subreddits from 2010-2019: "TwoXChromosomes, " "Askwomen, " "Askmen, " "OneY." We developed an initial codebook with expected themes, augmented with salient themes emerging from a random sampling of 10% of posts, and revised iteratively until adequate inter-rater agreement was reached; remaining posts were coded independently. RESULTS: Of 271 withdrawal-related queries, 19% were submitted by men; 81% referenced the contributor's own use of withdrawal. Salient themes included: concerns about pregnancy risk (52%), using withdrawal with additional contraception (49%), impact on personal life/relationship (27%), benefits/pleasure from using withdrawal (12%), when or how to effectively use withdrawal (7%), and problems encountered (3%). Posts to female-focused forums more frequently inquired about pregnancy risk, while those on men's forums inquired about when/how to use withdrawal (P<.01); themes were not associated with contributor gender. CONCLUSION: Withdrawal-related queries on Reddit are more frequently posted by women, the majority of whom want to better understand their risk of pregnancy with withdrawal. Research on operationalizing withdrawal and withdrawal-related pregnancy risk may help providers counsel patients and decrease their reliance on online forums.